Analisis Pengendalian Kualitas Kernel dengan Metode Peta Kontrol – R Pada PT. Inti Indosawit Subur - Agus Topo Subekti (Jurnal INOVATOR, 2020)
The problem in this research is using the control chart diagram - R whether the 2018 kernel product defects at PT. Inti Indosawit Subur is still under control ?, by using a causal diagram what factors cause the failure of kernel products at PT. Inti Indosawit Subur?. The purpose of this final project is to determine the defect rate of kernel products at PT. Inti Indosawit Subur is still under control or not through the control chart - R and to find out what factors cause the failure of kernel products at PT. Inti Indosawit Subur through a causal diagramThe data collection methods used in the writing of this study were field research (interviews and documentation) and literature study. The data analysis method used is the control chart - R to see abnormalities or deviations in the kernel quality data and cause and effect diagrams to analyze what are the causes of product defects.Based on the results of research and data processing, it is known that of the three quality standards of kernel products, two of them are out of control, namely dirt and shell (dirt content) and broken kernel (broken kernel). Therefore, the authors provide suggestions for the company to improve the quality of kernel products.